Innovative Strategies Using Gojek and Grab Digital Platforms to Boost Brand Sales - Partogi, Chris; Heru Riza Chakim, Mochamad; Mulyati; Bimantoro (Pandawan, 2025)
In the digital era, shifting consumer behaviors and advancing technology ne- cessitate innovative marketing strategies. This study examines how brands leverage on-demand platforms like Gojek and Grab to enhance sales, market reach, and engagement, situated within global digital transformation trends akin to platforms like Uber Eats. Employing a qualitative case study and literature analysis, it identifies strategies grounded in theories such as consumer loyalty and customer value, including location-based promotions (used by 70% of businesses), data-driven personalization, and loyalty programs (adopted by 80%). These approaches improve distribution and create personalized cus- tomer experiences, with reviews and analytics informing decisions. However, challenges like high commission fees and algorithm dependency, particularly for MSMEs, require strategic solutions. Findings highlight that platform col- laborations drive competitive advantage, mirroring global platform economies. This research offers actionable insights for MSMEs and enterprises to design effective digital strategies and recommends exploring platform applications in non F&B sectors for future studies, contributing to digital marketing literature and practice in dynamic markets.